Ultrastructural changes of mitochondrion in the contractile ventricular cardiomyocytes of rats under experimental conditions of chronic prenatal hypoxia. - Ivanchenko, M. V. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. Ultrastructure of mitochondria depends on the functional load on the organelle and is characterized by dynamic changes in the outer, and particularly the inner mitochondrial membrane, cristae and cause changes in the intensity of ATP synthesis and normal contractile function of the heart. Objective. Analysis of the ultrastructural rearrangement of mitochondria in the rat ventricular contractile cardiomyocytes at the prenatal ontogenesis in conditions of chronic intrauterine hypoxia. Methods. White rats were used as a material. Intrauterine hypoxia was modeled by intraperitoneal injection of sodium nitrite on the 10th and 21st day of pregnancy. Embryonic hearts on the 14th, 16th, 18th and 20th days of prenatal ontogenesis were investigated with the help of transmission electron microscopy. Packaging and quantitative density of mitochondria were estimated. Results. It was shown that during prenatal ontogenesis the structure of individual mitochondria and mitochondrial network significantly changes. Heterogeneity of the organelles and their localization in the cell reflects a specific response of mitochondria on the pathological process. On early stages of rat embryogenesis morphological and ultrastructural changes in mitochondrial network are more prominent in the contractile cardiomyocytes of the right ventricle comparing with the parameters of the left ventricle. In the same manner changes in the subsarcolemmal and intermyofibrillar regions are more significant than in the intracellular localized mitochondria and result in decrease of mitochondrial growth parameters and development of heterogeneity of organelles. Conclusion. Under the hypoxic conditions during rat prenatal ontogenesis the most significant processes of mitochondria destruction takes place in the subsarcolemmal and intermyofibrillar regions of cardiomyocytes of left ventricle.